Use of a generalized gamma additive model to determine the effect of monetary policy on the Nigerian stock market - Aako*†, O.L.; Agbolade*‡, O.A. (International Journal of Mathematical Analysis and Modelling, 2023)
This study looked at how monetary policy affected the Nigerian stock market’s performance from 2006 to 2020 using Generalized Additive Model for Location, Scale, and Shape (GAMLSS). The method expands the capabilities of linear, generalized linear and additive models. The All-Share Index was used to gauge the performance of the Nigerian stock market. Money supply, interest rate, exchange rate, and inflation rate were used to gauge monetary policy, which served as the explanatory variable. In order to choose the best fitted model, some selected GAMLSS family distributions in the positive real line, including the Generalized gamma, Gumbel, Weibull, and Log normal distributions, were fitted to the data. The Generalized Gamma (GG) distribution best fits the response variable, according to the AIC and BIC results. In order to ascertain how monetary policy affected the Nigerian Stock Market, GG in GAMLSS was employed. The study's conclusions demonstrate that whereas other variables have negative associations with the All-Share Index, the money supply has a positive link with it. The Nigerian Stock Market All-Share Index is significantly impacted by each of the explanatory variables.